Verbal correspondence: Effect of reinforcement and punishment probabilities due to question type (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
This study investigated the effect of reinforcement and punishment probabilities due to open (OQ) and closed (CQ) questions on verbal correspondence. Six university students played six games against a confederate, divided into rounds, in which participants bought a card and reported whether or not it was equal to the trump card that determined victory in the round. In comparison with previous studies, the number of cards elements to be reported was increased and the confederate’s reports were standardized. In CQ matches, the participants had to say whether or not they had the trump card. In OQ, they were asked to describe the card they bought in the round, with no indication of what the trump card was. Distorted reports were punished when there was checking, which occurred in one-fifth of the rounds. Replicating the literature, verbal correspondence was higher in OQ, as the distortions were concentrated in CQ, which showed the effect of the probability of reinforcement and punishment determined by question type.